2020
DOI: 10.2217/imt-2019-0205
|View full text |Cite
|
Sign up to set email alerts
|

Real-Life Effect of a Microcrystalline Tyrosine Adjuvanted Mite Immunotherapy in Patients with Allergic Rhinitis

Abstract: Aim: Evaluate the effectiveness and safety of immunotherapy with Acarovac Plus® in a 1-year prospective multicentered real-life study. Methods: A total of 118 adults with allergic rhinitis sensitized to Dermatophagoides received subcutaneous immunotherapy with Acarovac Plus. Treatment outcomes were evaluated at baseline, 6 months and 1 year after treatment initiation. Primary end point was the evolution of the combined symptom and medication score. Secondary end points included other effectiveness outcomes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…MCT has not shown toxic properties, although it is contraindicated in tyrosine metabolism disorders [ 90 ]. Currently, MCT is patented as an adjuvant for use in immunotherapy [ 93 ] and is integrated into glutaraldehyde allergoids for Dermatophagoides to help reduce allergic symptoms and diminish the use of relief drugs [ 94 , 95 , 96 , 97 ].…”
Section: Adjuvantsmentioning
confidence: 99%
“…MCT has not shown toxic properties, although it is contraindicated in tyrosine metabolism disorders [ 90 ]. Currently, MCT is patented as an adjuvant for use in immunotherapy [ 93 ] and is integrated into glutaraldehyde allergoids for Dermatophagoides to help reduce allergic symptoms and diminish the use of relief drugs [ 94 , 95 , 96 , 97 ].…”
Section: Adjuvantsmentioning
confidence: 99%
“…The evolution of allergen-specific immunotherapy: The near and far future 1 year of SCIT in adult patients with allergic rhinitis. 7 MLPA is a detoxified tool-like receptor-4 ligand that is commonly used in human vaccines and includes allergy ones. However, in the allergy field, the use of MLPA is rather limited.…”
Section: S U P P L E M E N T a R T I C L Ementioning
confidence: 99%
“…Furthermore, one of the most interesting properties of MCT is its rapid biodegradation, which allows us to minimize the risk of toxicity in the event of prolonged accumulation. A recent study demonstrated the effectiveness and safety of MCT adjuvant after 1 year of SCIT in adult patients with allergic rhinitis 7 . MLPA is a detoxified tool‐like receptor‐4 ligand that is commonly used in human vaccines and includes allergy ones.…”
mentioning
confidence: 99%
“…Here, we analysed the tolerability and safety during the updosing phase of a house dust mite (HDM) subcutaneous allergen-specific immunotherapy (SCIT) [1,2], marketed in Austria shortly before start of this study.…”
Section: To the Editorsmentioning
confidence: 99%